An Overview of Systematic Reviews of Randomized Controlled Trials on Acupuncture Treating Migraine - Xia-tian Zhang; Xin-yi Li; Chen Zhao; Ye-yin Hu; Yi-yi Lin; He-qing Chen; Zhao-feng Shi; Xiao-yu Zhang; Hong-cai Shang; Gui-hua Tian (Pain Research and Management)
Objectives. To review the evidence of acupuncture for acute and preventive treatment of migraine for further awareness of the effect of acupuncture for migraine. Design. An overview of systematic reviews and meta-analyses (SR/MAs) for randomized controlled trials. Material and Methods. We searched PubMed, Embase, the Cochrane Library, China Knowledge Resource Integrated Database, VIP Chinese Journal Full Text Database, WANFANG Data, and China Biology Medicine disc from their establishment to May 27, 2018. SR/MAs of randomized controlled trials comparing the effect of the acupuncture intervention with another treatment control in migraine patients were included. Results. 428 SRs were identified, and 15 of them were included. Only 4 SR/MAs were assessed by GRADE, which showed certainty of most evidence being low or very low. Assessed by AMSTAR-2, fourteen was critically low rating overall confidence in the results, and 1 was low rating overall confidence in the results. Evidence suggested that acupuncture has a significant advantage of pain improvement, efficacy, and safety relative to blank control, sham acupuncture, or drug treatment, but some of these results are contradictory. Conclusions. We found that acupuncture on treating migraine has the advantage for pain improvement and safety, but the quality of SR/MAs of acupuncture for migraine remains to be improved.